EJB 3.0 database persistence with Oracle Fusion Middleware 11g LITE build EJB 3.0 database persistent models with both Oracle JDeveloper and Enterprise Pack for Eclipse /: build EJB 3.0 database persistent models with both Oracle JDeveloper and Enterprise Pack for Eclipse. ([2011]) - Vohra, Deepak, 1966-
No abstract available